Trained Immunity as an Adaptive Branch of Innate Immunity - Vetvicka, Vaclav; Sima, Petr; Vannucci, Luca (International journal of molecular sciences, 2021)
The concept of trained immunity has become one of the most interesting and potentially commercially and clinically relevant ideas of current immunology. Trained immunity is realized by the epigenetic reprogramming of non-immunocompetent cells, primarily monocytes/macrophages and natural killer (NK) cells, and is less specific than adaptive immunity; therefore, it may cross-protect against other infectious agents. It remains possible, however, that some of the observed changes are simply caused by increased levels of immune reactions resulting from supplementation with immunomodulators, such as glucan. In addition, the question of whether we can talk about trained immunity in cells with a life span of only few days is still unresolved.
Keywords: homeostáza; Macrophages; Immunity, Cellular; beta-glukany; náchylnost k nemoci; makrofágy; beta-Glucans; zvířata; buněčná imunita; monocyty; Homeostasis; Animals; lidé; Leukocytes; lymfocyty; Disease Susceptibility; Lymphocytes; adaptivní imunita; Humans; Immunity, Innate; přirozená imunita; Killer Cells, Natural; buňky NK; Adaptive Immunity; Monocytes; leukocyty